Endoscopic orbital floor decompression with preservation of the inferomedial strut. Issue 1 (2nd October 2013) - Bleier, Benjamin S.; Lefebvre, Daniel R.; Freitag, Suzanne K.
<x xml:space="preserve">Abstract</x> Background Medial and inferior orbital decompression is most commonly performed in the setting of dysthyroid orbitopathy. Diplopia represents the most common complication and may be minimized through the preservation of a bony inferomedial strut (IMS). Historically, this has required a transconjunctival approach due to the technical demands of performing an isolated orbital floor decompression using endoscopic instrumentation. Here we describe a novel technique of a purely endoscopic orbital floor decompression with reliable preservation of the IMS. Methods Description of a novel surgical technique for endoscopic orbital floor decompression with IMS preservation using frontal sinus instrumentation visualized by a 70‐degree endoscope. Results We have successfully used this technique in 12 orbits with 100% preservation of the bony inferomedial strut and no complications. The extent of decompression and width of the residual strut may be fine tuned as needed to optimize results. Conclusion Orbital floor decompression with IMS preservation may be reliably performed using purely endoscopic techniques. Successful completion of this procedure requires the adaptation of standard frontal sinus instrumentation to the maxillary sinus roof and thus may be readily mastered by any endoscopic surgeon comfortable with frontal sinus techniques.